Research on 6G standardization of International Telecommunications Union（ITU） - Yan WANG; Ying PENG (Dianxin kexue)
The International Telecommunications Union (ITU), as the authoritative international standardization organization in the field of information and communications (ICT), is leading the pace of the work in technology research and standardization of 6G.With the joint efforts of various parties in the global industry, it expected to officially release international standards for 6G around 2030 and promote its commercialization.Firstly, the basic information and organizational structure of ITU was introduced.And the current progress of ITU’s IMT-2030(6G) standardization work including the Recommendation “ITU-R M.[IMT.Framework for 2030 and Beyond]”, Report “Future technology trends of terrestrial IMT systems towards 2030 and beyond” and etc., as well as subsequent standardization research were analyzed.In addition, the impact of ITU’s 6G standardization work on the mobile communication and industries was also analyzed.The standardization work of 6G in ITU can not only promote technological changes and upgrades for the new generation of mobile communication systems, but also drive the transformation and development of the industry ecosystem.